2016
DOI: 10.1371/journal.pone.0151705
|View full text |Cite|
|
Sign up to set email alerts
|

Relative Importance and Additive Effects of Maternal and Infant Risk Factors on Childhood Asthma

Abstract: BackgroundEnvironmental exposures that occur in utero and during early life may contribute to the development of childhood asthma through alteration of the human microbiome. The objectives of this study were to estimate the cumulative effect and relative importance of environmental exposures on the risk of childhood asthma.MethodsWe conducted a population-based birth cohort study of mother-child dyads who were born between 1995 and 2003 and were continuously enrolled in the PRIMA (Prevention of RSV: Impact on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 57 publications
4
56
0
1
Order By: Relevance
“…72 Additionally, studies such as the Prevention of RSV: Impact on Morbidity and Asthma cohort found cumulative effects of the exposure to antibiotics on the risk of childhood asthma. 73 These studies support the association between antimicrobials during pregnancy, delivery and infancy with immune-mediated disease, and the potential role of perturbations in microbial community composition in increased disease risk. 3 …”
Section: Discussionsupporting
confidence: 62%
“…72 Additionally, studies such as the Prevention of RSV: Impact on Morbidity and Asthma cohort found cumulative effects of the exposure to antibiotics on the risk of childhood asthma. 73 These studies support the association between antimicrobials during pregnancy, delivery and infancy with immune-mediated disease, and the potential role of perturbations in microbial community composition in increased disease risk. 3 …”
Section: Discussionsupporting
confidence: 62%
“…In this context, human microbiome may play an important role by activating the maturation of the host immune system. Accordingly, in pregnancy, maternal antibiotic use and urinary tract infections are linked with higher risk of childhood asthma . Furthermore, exposure to microbes in utero due to respiratory viral infections in pregnant women with asthma is associated with higher frequency of wheezing in their infants .…”
Section: Origins Of Asthma and Allergic Rhinitismentioning
confidence: 99%
“…Antibiotic use in children has been associated with an altered microbiome (Korpela, Salonen, Virta, Kekkonen, & de Vos, 2016) and increased risk of diseases like obesity (Mbakwa et al, 2016) and asthma (Wu et al, 2016). Thus, prevention of AAD by strengthening the microbiome using concomitant probiotics is a highly attractive option for children and infants undergoing antibiotic therapy.…”
Section: Review Commentarymentioning
confidence: 99%